Social media platforms as discursive environments in the context of Russo-Ukrainian war - Soklakov, Maksym (Ukrainian Cultural Studies, 2025)
Background. Social media platforms have become primary channels of media consumption and key battlegrounds for information warfare. Their socio-technical affordances democratize cultural production–fueling new forms of expression, political mobilization, and even participation in military operations-while also enabling large-scale propaganda, cultural influence, and historical documentation on both sides of the Russo-Ukrainian frontline. Operating beyond state control, these platforms serve not only tactical communication needs but also broader processes of identity-building, cultural resistance, and the preservation of collective memory. Intensified by the protracted conflict and ongoing mediatization trends, this unique digital landscape demands urgent socio-humanitarian analysis. Methods. This study employs a multi-method design to explore cultural production and discursive practices during the Russo-Ukrainian War. We mapped social media affordances via media-studies frameworks; harvested public posts, metadata, hashtags, and profiles using OSINT; and conducted informal content analysis. Narrative and critical discourse analyses revealed story arcs and ideological strategies, while memory and spatial analyses examined commemorative posts and symbolic redefinitions of urban spaces. Results. The Russo-Ukrainian war is highly mediatized, with smartphones and social media turning civilians into active participants. These platforms enable content creation, OSINT, propaganda, and resistance, reshaping cultural practices and information flows. In occupied areas, competing media narratives emerge-occupation channels seek to legitimize control, while grassroots resistance documents realities and reinforces Ukrainian identity. Social media becomes both a battlefield and an archive of war. Conclusions. Social media platforms shape the digital image of the city through the production of everyday content. Media content is used for cultural influence and to establish control over the newly formed digital public sphere. The publication of digital content is, in essence, a process of cultural production in social media. Therefore, social media constitute a valuable source for research, as they allow us to study the transformations that occur during the occupation, as well as to predict the development of reintegration policies.